High Prevalence of Gastroesophageal Reflux Disease in Parkinson’s Disease: A Questionnaire-Based Study - Tetsuya Maeda; Ken Nagata; Yuichi Satoh; Takashi Yamazaki; Daiki Takano (Parkinson's Disease)
The aim of this study is to investigate the frequency and clinical features of gastroesophageal reflex disease (GERD) in Parkinson’s disease (PD). Consecutively recruited PD patients and controls were questioned about heartburn and GERD with a questionnaire. In PD patients, disease duration and severity, quality of life, and nonmotor symptoms were also examined and then the clinical features of GERD were analyzed. A total of 102 patients and 49 controls were enrolled and 21 patients and 4 controls had heartburn, significantly frequent in PD. The prevalence rate of GERD was 26.5% in PD and the odds ratio was 4.05. Heartburn, bent forward flexion, and wearing-off phenomenon were frequent, and scores of UPDRS, total and part II, PD questionnaire-39, and nonmotor symptom scale were significantly higher in PD patients with GERD than without GERD. Multiple logistic regression analysis revealed statistical significance in UPDRS part II and nonmotor symptom scale. This study suggests that GERD is prevalent in PD. Deterioration of daily living activities and other nonmotor symptoms can imply the presence of GERD. Because clinical symptoms of GERD are usually treatable, the management can improve the patient’s quality of life. Increased attention should be given to detect GERD in PD.